CEO Overconfidence as Moderator of Sales Growth, Interest Coverage, Fixed Asset Intensity to Financial Distress - Slamet, Franki; Ramadhan, Yanuar (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 18 No 2 (2023)DO - 10.24843/JIAB.2023.v18.i02.p08, 2023)
This study seeks to explore the influence of certain factors, namely company growth, interest coverage ratio, and fixed asset intensity, on a company's financial health or distress. We pay special attention to the potential role of CEO overconfidence as a variable that might change or moderate these influences. Drawing from a quantitative approach, we used publicly available financial statements of primary consumer goods companies listed on the Indonesia Stock Exchange from 2017 to 2021. Our findings suggest that company growth and the value of fixed assets play roles in determining financial distress, but the interest coverage ratio does not. Moreover, when factoring in CEO overconfidence, we found it changes the way company growth and fixed assets relate to financial distress. Yet, this CEO trait doesn’t alter the relationship between the interest coverage ratio and financial distress. Keywords : company growth, interest coverage ratio, fixed asset intensity, ceo overconfidence, financial distress